PENGARUH PROFITABILITAS, DEBT TO ASSET RATIO DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Frestin Chrisnanti; Michael (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to analyze empirically the influence of profitability, debt to asset ratio, liquidity, firm size, dividend policy, earning per share, institutional ownership and managerial ownership on firm value. Sample of this research are 95 non financial companies in Indonesia Stock Exchange, selected using purposive sampling method during 2018 until 2020. Data were analyzed using multiple regression method. The empirical evidence of this research indicateded that profitability, debt to asset ratio, and institutional ownership have influence to firm value. High profitability can be a positive signal for investors regarding the company's future prospects. High debt to asset ratio indicates that the company is able to use debt to increase firm value. High share institution ownership can assist in supervising the company While other independent variables such as liquidity, firm size, dividend policy, earning per share, and managerial ownership have no influence towards firm value in the company because because these variables do not have sufficient impact to influence investors in conducting funding